2020
DOI: 10.3389/fpsyg.2020.00723
|View full text |Cite
|
Sign up to set email alerts
|

Swearing as a Response to Pain: Assessing Hypoalgesic Effects of Novel “Swear” Words

Abstract: Previous research showing that swearing alleviates pain is extended by addressing emotion arousal and distraction as possible mechanisms. We assessed the effects of a conventional swear word ("fuck") and two new "swear" words identified as both emotion-arousing and distracting: "fouch" and "twizpipe." A mixed sex group of participants (N = 92) completed a repeated measures experimental design augmented by mediation analysis. The independent variable was repeating one of four different words: "fuck" vs. "fouch"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 30 publications
6
38
0
Order By: Relevance
“…bad, hate, sick, suffer) in the posts of users showing signs of depression, where the discourse of users not showing any signs contains more sexual-related content, addressing our RQ2. These findings are consistent with the existing literature from psychology (Stephens and Robertson, 2020;Everaert et al, 2017;Beck and Haigh, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…bad, hate, sick, suffer) in the posts of users showing signs of depression, where the discourse of users not showing any signs contains more sexual-related content, addressing our RQ2. These findings are consistent with the existing literature from psychology (Stephens and Robertson, 2020;Everaert et al, 2017;Beck and Haigh, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…The use of offensive language could be an emotion regulation strategy through which depressed individuals relieve some of their distress. Similarly, pain and distress studies indicate that the use of offensive language when experiencing pain significantly diminishes the level of pain experienced (Stephens and Robertson, 2020), suggesting that the use of offensive language can relieve distress.…”
Section: Resultsmentioning
confidence: 97%
“…This would theoretically lead to attention-mediated reduction in BIS activity and consequent disinhibition. Consistent with this suggestion, previous research has shown that swearing is rated as distracting (Stephens & Robertson, 2020). Henceforth, we refer to this as the “distraction pathway” for swearing-induced state disinhibition.…”
Section: Introductionsupporting
confidence: 74%
“…That most languages include swear words (van Lancker & Cummings, 1999) suggests they fulfil one or more useful functions and researchers have begun to evidence a variety of beneficial effects of swearing. Repeating a swear word has been found to alleviate the physical pain of immersing one’s hand in ice cold water (Robertson et al, 2017; Stephens et al, 2009; Stephens & Robertson, 2020; Stephens & Umland, 2011) and the social pain of being ostracised (Philipp & Lombardo, 2017). Swearing also augments persuasiveness (Scherer & Sagarin, 2006), credibility (Rassin & Heijden, 2005) and has been shown to benefit physical tasks that rely on strength and power (Stephens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that a patient needs to use an actual swear word, not a made up or bad sounding word, to elicit the pain and physical performance improvements. Stephens et al [ 17 ] discovered that pain tolerance and pain threshold improved in subjects that repeated the F-word , but pain metrics did not improve when subjects repeated the made up swear words “fouch” or “twizpipe”.…”
Section: Introductionmentioning
confidence: 99%